Aplikasi “GENTA” Pers Mahasiswa Universitas Kristen Petra Berbasis Android untuk Menambah Aksesibilitas Website - Atmodjo, Kristoforus Gumilang Kurniawan; Andjarwirawan, Justinus; Purbowo, Anita Nathania (Jurnal Infra, 2018)
Nowadays, most people have smartphone which connected to internet. This situation increase people’s demand of information through application. At Petra Christian University there is one of the student organizations that is authorized to publish news about campus environment, namely Student Press GENTA. The Petra Christian University Student Press has two types of products, namely GENTA online and GENTA magazine.During this time, GENTA Online, where as a place of publication news about student activities, which use the media website, still received less attention from its users. While GENTA magazine, the number of print magazines, less covering the entire student. GENTA also has a Research and Development division, which aims to share questionnaires, but is still manual using paper.This GENTA application was created so that GENTA can be accessed more by Petra Christian University’s students and staff and reduce paper use for the questionnaire from GENTA's research and development division. This application is made using Java and PHP programming language, the database used is MySQL, and the library used is Retrofit and Realm. With this application, students and staff of Petra Christian University can more easily access GENTA Online and GENTA magazine.